STRUCTURAL EVOLUTION OF THE CHEKA PLUTON (SOUTHERN URALS): PETROMAGNETIC STUDIES AND FRACTURE ANALYSIS - P. A. Shestakov; A. Yu. Kazansky; A. V. Tevelev; N. V. Pravikova; E. V. Koptev; E. A. Volodina; A. A. Borisenko; I. A. Kosheleva (Геодинамика и тектонофизика, 2024)
The Cheka pluton, located in the Magnitogorsk megazone of the Southern Urals and composed of the alkaline granitoids, is meridionally elongated (1–2)×6.5 km. The fracture and anisotropy of magnetic susceptibility analysis was made on the Cheka pluton for the first time. The study materials comprise fracture measurements and core samples. The fractures were classified as either prototectonic or tectonic using the Stereonet software. The prototectonic fractures were classified into three standard types in accordance with the system proposed by G. Cloos: S, Q, and L. The system of tectonic fractures corresponds to the Riedel model, which confirms the formation of the pluton as a dextral magmatic strike-slip duplex supposed earlier. The analysis of magnetic mineralogy revealed that the most prevalent magnetic mineral is fine- to-medium-grained magnetite. Using the anisotropy of magnetic susceptibility data, the main direction of melt flow during the formation of the pluton was determined to be 36° NE. This direction is in close alignment with the orientation of one of the prototectonic fracture systems, which has a strike azimuth of 39° NE. The constructed complex structure model indicates that the Triassic granitoid plutons of the Magnitogorsk megazone were most likely formed during the right-lateral transpression, associated with a local strike-slip fault-related extension zone. These conditions are generally consistent with the Triassic rifting and dextral strike-slip motion in the Southern Urals.